Detection Limit Of Carbamate Pesticides Biosensors Based Enzyme Acetylcholinesterase And Cholin Oxidase On Platinum Electrode - -, Mashuni (Jurnal Progres Kimia Sains, 2011)
The presence of carbamate pesticides in environmental and food poses a potentialhazard to human health and there is a growing interest in their rapid and accurate determinationfor food safety and environmental monitoring. The aim of this research is to designelectrochemical biosensor for analyzingcarbamate pesticides residue in food material.Acetylcholinesterase (AChE) and cholin oxidise (ChO) enzyme was immobilized at platinum (Pt)wire plated with membrane materials of SA 5%, 10%, 15% and GA 25%. Result of this researchshow that for cellulose acetate (SA) 5% the detection limit is 10-7,7 M, for SA 10% the detectionlimit is 10-8,7 M, for SA 15% the detection limit is 10-7,6 M. This a results is approximately equal to2,2 ppb). ), which means that this biosensor is very sensitive for determining carbamatespesticides residue where its detection limit is comparable to to the detection limit of conventionalinstrument such as Gas Chromatography (GC) and High Pressure Liquid Chromatography(HPLC), i.e. respectively 1,5 ppb and 2,0 ppb.